Komunikasi Profetik dalam Mengajak Santri Non Mukim Menghafal al-Qur’an (Studi Kasus di Pondok Pesantren al-Ittifaqiah Indralaya Ogan Ilir Sumatera Selatan) - Yenrizal Yenrizal; Reza Aprianti; Zulva Hurin'in (Jurnal Studi Sosial dan Politik, 2018)
Communication is very important role for human life in socializing even in the teaching and learning process. This study describes prophetic communication in Islamic boarding school which aims to understand the process of prophetic communication in inviting non-resident Islamic Boarding School students to memorize the Qur'an. This study presents two substance problems, namely: 1) How does the implementation of prophetic communication in inviting non-resident students to memorize Al-Qur'an at Al-Ittifaqiah Islamic Boarding School ?. 2) What are the obstacles encountered when inviting non-resident students to memorize the Qur'an? To obtain answers to the problems above, this study uses descriptive qualitative research methods of analysis that is grouping data according to their categories and outlining all concepts related to the research discussion. The data sources of this study are non-resident students and tahfizh teachers of Al-Ittifaqiah Islamic Boarding School. Furthermore, data collection methods used are through observation, interviews, and documentation. The data obtained will be analyzed using data reduction, data presentation, and drawing conclusions. This research uses the theory of message reinforcement (reinforcement theory). The results of this study indicate that prophetic communication conducted by Al-Ittifaqiah Islamic Boarding School, namely the teachers communicate well (ma'ruf) to their students, so that it has a good effect on the students. Then provide motivation that can increase the spirit of memorizing the students. Socialization was also held by Islamic boarding schools by giving awards to high-achieving students. While the inhibiting factor in inviting non-resident students to memorize the Qur'an is, it is difficult to communicate directly with students because of the influence of distance. Then the residential environment that does not support where non-resident students do not live in boarding school resulting negligence in memorizing and inhibiting the process of memorizing students.